Politics, Utopia and Disillusionment in NoViolet Bulawayo’s We Need New Names (2013) - Babacar Diakhate (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2019)
This article brings to light political disillusionment in Zimbabwe under the presidency of Robert Mugabe.  In We Need New Names (2013) NoViolet Bulawayo has explored how political disillusionment has triggered off the search for utopia in relation to migration.  This paper portrays Darling, a victim of Mugabe’s Operation Murambatsiva, has journeyed to America so as to find other opportunities.  It also shows that in fleeing poverty in Zimbabwe to search for a better life in America, disillusionment is unavoidable because utopia is associated with disillusionment.